Aerobic Exercise, Ball Sports, Dancing, and Weight Lifting as Moderators of the Relationship between Stress and Depressive Symptoms: An Exploratory Cross-Sectional Study with Swiss University Students. Issue 3 (December 2014) - Gerber, Markus; Brand, Serge; Elliot, Catherine; Holsboer-Trachsler, Edith; Pühse, Uwe
This exploratory study was designed to compare four types of exercise activities in Swiss university students. A sample of 201 medical students (136 women, 65 men; M age = 23.2 yr., SD = 2.4) and 250 exercise and health sciences students (144 women, 106 men; M age = 22.3 yr., SD = 2.2) participated in the study. They completed the Perceived Stress Scale, the Depression Scale, and the Office in Motion Questionnaire. Interaction effects between stress and exercise activities were analysed using hierarchical regression analyses, after controlling for age, sex, and academic discipline. Frequent participation in ball sports and dancing were associated with decreased depressive symptoms among students with elevated perceived stress, whereas no such relationship existed among their peers with lower perceived stress. No stress-moderating effect was found for aerobic exercise. Weight lifting was only associated with lower depressive symptoms among students with low perceived stress. The present findings suggest that, among Swiss university students, certain exercises may have better potential to moderate the relationship between perceived stress and depressive symptoms than others. Future research could analyze whether personalized exercise programs created to satisfy participants' individual needs are more beneficial for stress management.